The Teaching English Reading Skill to Senior Vocasional School Students in Samarinda - Tardik Arbi Wijaya (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2021)
Reading is one of the abilities of English lessons, the author tried to explore the reading lessons that carried out at SMK Negeri 15 Samarinda. The thing we wanted to know is what strategies are used to teach reading skill at the school and how to implement it. This research used descriptive qualitative research. The subjects in this study were four English teachers at SMK Negeri 15 Samarinda. The instrument in this research were interviews and documentation. In the section on the results of the findings obtained, it shows that each teacher has a different strategy for teaching students in the classroom and the teacher also uses different implementations teaching technique. Basically, the teacher uses the lesson plan and syllabus and the semester program that has been agreed upon to become teaching material in the classroom.